Peranan Hukum Pidana Pada Penyelesaian Sengketa Pembatalan Sertifikat Hak Atas Tanah Oleh Kepala Kantor Wilayah Badan Pertanahan Nasional - Eleonora Sinay Moniung; Keyzha Natakharisma (Universitas Mahendradatta, 2020)
Land registration in Indonesia uses a negative publication system. In a negativepublication system, the state only passively accepts what is stated by the party requestingregistration. As a result of this system, every person has the right to make a claim against the landcertificate to be canceled, this land tends to be used by the land mafia to cancel the land incollaboration with an individual. BPN officials therefore in this study discuss the extent to whichcriminal law regulates these acts. This study uses a normative juridical approach. The purpose ofthe term,